Venture capital & the finance of innovation - Metrick, Andrew; Yasuda, Ayako (Wiley, 2011)
"This useful guide walks venture capitalists through the principles of finance and the financial models that underlie venture capital decisions. It presents a new unified treatment of investment decision making and mark-to-market valuation. The discussions of risk-return and cost-of-capital calculations have been updated with the latest information. The most current industry data is included to demonstrate large changes in venture capital investments since 1999. The coverage of the real-options methodology has also been streamlined and includes new connections to venture capital valuation. In addition, venture capitalists will find revised information on the reality-check valuation model to allow for greater flexibility in growth assumptions."